Transmitter-Side Wireless Information- and Power-Transfer in Massive MIMO Systems - Nasir, Ali Arshad; Tuan, Hoang Duong; Duong, Trung Q.; Hanzo, Lajos (IEEE transactions on vehicular technology, 2020)
Both time-switching (TS) and power splitting has been used at the receiver for wireless information and power transfer in the downlink of massive multiple-input-multiple-output systems. By contrast, this correspondence adopts the transmit-TS approach, where the energy and information are transferred over different fractions of a time slot. Our goal is to jointly optimize the transmit-TS factor and power allocation coefficients during energy and information transfer for maximizing the users' minimum throughput subject to transmit power and minimum harvested energy constraints. This nonconvex problem is solved by our path following algorithm. Our simulation results demonstrate the benefits of the proposed transmit-TS algorithm, which easily doubles the throughput compared to that of the existing techniques.